2011
DOI: 10.1089/ten.tea.2010.0125
|View full text |Cite
|
Sign up to set email alerts
|

Vascularization of the Dermal Support Enhances Wound Re-Epithelialization by In Situ Delivery of Epidermal Keratinocytes

Abstract: Despite significant advances in management of severe wounds such as burns and chronic ulcers, autologous split-thickness skin grafts are still the gold standard of care. The main problems with this approach include pain and discomfort associated with harvesting autologous tissue, limited availability of donor sites, and the need for multiple surgeries. Although tissue engineering has great potential to provide alternative approaches for tissue regeneration, several problems have hampered progress in translatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
30
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(35 citation statements)
references
References 52 publications
3
30
0
2
Order By: Relevance
“…Fibrin has been widely used to create vascularized tissue constructs for skin [62,63], adipose tissue [63][64][65][66], bone [67][68][69], cartilage [70], skeletal muscle [71], retina [72], liver [73], and cardiovascular [74,75] applications. The wide use of fibrin in vascularized tissues is due to its excellent pro-angiogenic properties.…”
Section: Fibrinmentioning
confidence: 99%
“…Fibrin has been widely used to create vascularized tissue constructs for skin [62,63], adipose tissue [63][64][65][66], bone [67][68][69], cartilage [70], skeletal muscle [71], retina [72], liver [73], and cardiovascular [74,75] applications. The wide use of fibrin in vascularized tissues is due to its excellent pro-angiogenic properties.…”
Section: Fibrinmentioning
confidence: 99%
“…For example, Integra™, which was designed to rebuild the dermal substrate [11,12]. However, the main component of Integra was still the collagen/chondroitin-6-sulfate composite [13,14], the silicone sheet was just used to protect the collagen-based scaffold.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that keratinocytes, when placed in a suitable microenvironment, are able to regenerate multi-lineage skin in mice [7]. Moreover, the transplanted keratinocytes facilitate the formation of blood vessels [8]. In addition, skin grafting has been used for the treatment of burns and chronic leg ulcers, which can promote faster re-epithelialization of partial thickness wounds [9][10][11][12].…”
mentioning
confidence: 99%